The impact of carbon finance, renewable energy, and environmental knowledge on load capacity factor - Zhang, Long; M Aldeehani, Talla; Riaz, Samina; Khan, Aisha; Khudoykulov, Khurshid (Transformations In Business & Economics, 2025)
Load capacity factor is a comprehensive indicator which compares biocapacity and ecological footprint to track an environmental threshold. Scholars observe that, with rising environmental pollution, the load capacity factor decreases. The existing literature empirically measures environmental degradation through over-explored proxies such as ecological footprint, carbon emissions, GHG emissions, and nitrogen emissions. Because of the proxies used, the supply side of environmental problems is often neglected. This study addresses this gap by investigating renewable energy, environmental knowledge, and carbon finance, and their influence on load capacity factor in China. A nonlinear autoregressive distributed lag (NARDL) technique is used to evaluate the associations. The results show that renewable energy output and consumption, environmental knowledge, carbon finance, and population growth have positive relationships with load capacity factor in China. Therefore, the Chinese government must encourage biomass use and investment in renewable energy forms to restrict emissions.